Some more properties and remarks about keys for relation scheme - Thuần, Hồ; Souad, Souafi; Djamila, Mohamed Benkada (Journal of Computer Science and Cybernetics, 2016)
In this paper we prove some additional properties of keys and superkeys for relation schemes. Basing on these properties, some algorithms finding keys for relation schemes are improved and their complexities are estimated. Finally, some remarks on the translations of relation schemes are given.